Hospital capacity reporting in Germany during Covid-19 - Reif, Simon; Schubert, Sabrina (Journal of Economic Behavior & Organization, 2024)
During the COVID-19 pandemic, hospitals faced a unique predicament. Hospital care was urgently needed and society took efforts to prevent overwhelming hospitals. However, hospitals in case-based reimbursement schemes faced financial problems because of canceled elective care visits and government regulations to keep capacity free for Covid-19 patients. Therefore, emergency financing measures were implemented in many countries. We analyze how hospitals in Germany responded to a scheme that provided financial support if the intensive care unit (ICU) occupancy rate in a county exceeded 75%. The scheme distributed over seven billion euros to hospitals and was notable because financial support depended on a measure (ICU occupancy rate) that hospitals could directly influence. To analyze hospitals’ reactions to this scheme, we employ event study analyses comparing ICU capacity before and after regions became eligible. We find no evidence of strategic reporting at an economically meaningful and hence empirically detectable scale.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Covid; Financial support programs; Hospitals; Misreporting